2002
DOI: 10.1002/art.10368
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to crystalline silica and risk of systemic lupus erythematosus: A population‐based, case–control study in the Southeastern United States

Abstract: Objective. Crystalline silica may act as an immune adjuvant to increase inflammation and antibody production, and findings of occupational cohort studies suggest that silica exposure may be a risk factor for systemic lupus erythematosus (SLE). We undertook this population-based study to examine the association between occupational silica exposure and SLE in the southeastern US.Methods. SLE patients (n ‫؍‬ 265; diagnosed between January 1, 1995 and July 31, 1999) were recruited from 4 university rheumatology pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
131
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(136 citation statements)
references
References 48 publications
3
131
0
2
Order By: Relevance
“…This may reflect a true predominance of SLE and SSc among First Nations females, and is consistent with previous studies of SARD in First Nations populations, which also reported a genetic predisposition to autoimmune disorders and more severe disease phenotypes (7)(8)(9)(10)(11). It is interesting, however, to hypothesize that this increased prevalence is a result of environmental exposures in a population predisposed to SARD, since, for example, silica exposure has been suggested as an environmental trigger for SARD (30,31). Although a protective factor conferring improved survival could also increase prevalence estimates, this seems less likely given the more severe disease phenotypes and difficulties accessing health care reported in First Nations populations.…”
Section: Discussionsupporting
confidence: 89%
“…This may reflect a true predominance of SLE and SSc among First Nations females, and is consistent with previous studies of SARD in First Nations populations, which also reported a genetic predisposition to autoimmune disorders and more severe disease phenotypes (7)(8)(9)(10)(11). It is interesting, however, to hypothesize that this increased prevalence is a result of environmental exposures in a population predisposed to SARD, since, for example, silica exposure has been suggested as an environmental trigger for SARD (30,31). Although a protective factor conferring improved survival could also increase prevalence estimates, this seems less likely given the more severe disease phenotypes and difficulties accessing health care reported in First Nations populations.…”
Section: Discussionsupporting
confidence: 89%
“…The issue of latency was also addressed by Parks et al (2002), who evaluated occupational exposure to silica and the risk of systemic lupus erythematosus (SLE). In this population-based, case-control study, the authors observed an association between silica and SLE, with medium or high-level silica exposures found in individuals working in farming or trades.…”
Section: Discussionmentioning
confidence: 99%
“…Intrapulmonary deposition of silica results in a granulomatous inflammatory response that progresses to interstitial fibrosis, as well as systemic immune deficits (1)(2)(3)(4). Although significant efforts have been made through industrial hygiene standards to control ambient exposures, silicosis remains a prevalent health problem, particularly in developing nations.…”
mentioning
confidence: 99%